A sensational illusion: vision-touch synaesthesia and the rubber hand paradigm. - Davies, A; White, R (2013)
For individuals with vision-touch synaesthesia, the sight of touch on another person elicits synaesthetic tactile sensation on the observer's own body. Here we used the traditional rubber hand paradigm (Botvinick and Cohen, 1998) and a no-touch rubber hand paradigm to investigate and to authenticate synaesthetic tactile sensation. In the traditional rubber hand paradigm, the participant views a prosthetic hand being touched by the Examiner while the participant's hand - hidden from view - is also touched by the Examiner. Synchronous stimulation of the prosthetic hand and the participant's hidden hand elicits the rubber hand illusion. It may seem to the participant that she is feeling touch at the location of the viewed prosthetic hand - visual capture of touch, and that the prosthetic hand is the participant's own hand - illusion of ownership. Thus, for participants who experience the traditional rubber hand illusion, tactile sensation on the participant's hidden hand is referred to the prosthetic hand. In our no-touch rubber hand paradigm, the participant views a prosthetic hand being touched by the Examiner but the participant's hand - hidden from view - is not touched by the Examiner. Questionnaire ratings indicated that only individuals with vision-touch synaesthesia experienced the no-touch rubber hand illusion. Thus, synaesthetic tactile sensation on the (untouched) hidden hand was referred to the prosthetic hand. These individuals also demonstrated proprioceptive drift (a change, from baseline, in proprioceptively perceived position) of the hidden hand towards the location of the prosthetic hand, and a pattern of increased proprioceptive drift with increased trial duration (60 sec, 180 sec, 300 sec). The no-touch rubber hand paradigm was an excellent method to authenticate vision-touch synaesthesia because participants were naïve about the rubber hand illusion, and they could not have known how they were expected to perform on either the traditional or the no-touch rubber hand paradigm.